The Effect of Customer Reviews and Star Sellers on Purchasing Decisions at Shopee: The Role of Purchase Intention as a Moderating Variable in Balinese Students - Widiari, Ni Komang Intan Widiari; Anggreni, Anak Agung Tisa; Bagenda, Samuel Victor Eliezer (PT. Global World Scientific, 2023)
This study aims to analyze the effect of Customer Review and Star Seller variables on consumer purchasing decisions on the Shopee e-commerce platform. The population in this study were consumers who had made purchases at Shopee, with samples taken using purposive sampling techniques, namely consumers who provided product reviews. The variables studied consist of independent variables, namely Customer Review (X1) and Star Seller (X2), moderating variables, namely Purchase Intention (M), and the dependent variable Purchase Decision (Y). The analysis technique used is multiple linear regression with moderation of purchase intention as a moderating variable. The results of hypothesis testing show that the Customer Review variable has a significant positive effect on consumer purchasing decisions, while Star Seller does not show a significant effect. However, a significant interaction exists between Customer Review and purchase interest, strengthening its influence on purchasing decisions. The moderation regression test revealed that purchase intention plays a role in strengthening the effect of Customer Review on purchasing decisions, with a significant X1×M interaction coefficient. In contrast, the interaction between Star Seller and purchase interest shows a more minor but significant effect. The simultaneous test (F-test) shows that the two independent variables, Customer Review and Star Seller, influence consumer purchasing decisions. The coefficient of determination (R²) of 0.249 indicates that the two independent variables contribute 24.9% to consumer purchasing decisions. This finding emphasizes the importance of product review quality in influencing purchasing decisions in e-commerce.